Perceived values as determinants of in-app purchase intentions in mobile games - Blasa-Cheng, Angelique C. (Animo Repository, 2019)
Despite the growing use of mobile game applications, revenue in-app mobile game purchases remain relatively small in percentage. Little information is available on the motivation of mobile game players to spend in-game applications. This paper explores the determinants of in-app purchases using the perceived value model in the context of mobile game applications. The study utilized the response of 117 game players belonging to the smartphones-using group age. Linear regression was used to determine the relationships of perceived values (playfulness, access flexibility, connectedness, good price, and value for money) to in-app purchase intentions. Results showed that only the rewards derived by mobile game players from playing the game were the only factor positively affecting in-app purchase intentions. Future studies can further explore other factors affecting the motivation of mobile game players in purchasing in-app.